Delayed activation of the primary orbitofrontal cortex in post-traumatic anosmia. (5th December 2016) - Lee, Vincent Kyu; Nardone, Raffaele; Wasco, Fern; Panigrahy, Ashok; Zuccoli, Giulio
Abstract: Background : Functional magnetic resonance imaging may help in elucidating the pathophysiology of post-traumatic anosmia. Method : Using an fMRI olfactory stimulus paradigm, this study compared BOLD activation of the brain in a 21-year old male research subject with post-traumatic anosmia and a 19-year old male normal healthy control participant. Outcomes : A delayed activation of the primary orbitofrontal cortex was found in the subject with traumatic anosmia, which may represent a crucial pathophysiological mechanism in the subject with traumatic anosmia due to axonal injury or traumatic transection at the lamina cribrosa level. Discussion : In healthy subjects the activation of secondary cortical areas may be due to the habituation effect in the primary olfactory cortex. This raises the possibility that, in the absence of secondary activation areas—that may act as a feed-back habituation or desensitization in the patient—one of the primary response areas is activated over the longer period of stimulation. The failed activation of these secondary areas in the patient may cause a feed-back habituation or desensitization in the patient and could also play a role in the disturbed perception of odours.